A COMPARATIVE REVIEW OF CONTEMPORARY APPROACHES TO EMOJI SEMANTICS (SCIENCE TIME JOURNAL, 2026)
This article examines contemporary approaches to emoji semantics in digital communication. The study focuses on three major theoretical frameworks: cognitive, pragmatic, and semiotic approaches. Through a qualitative comparative analysis of recent linguistic research, the paper identifies the key principles, strengths, and limitations of each approach. The findings demonstrate that emoji function as multimodal meaning-making units that extend beyond traditional linguistic boundaries. It is argued that emoji semantics is inherently dynamic, context-dependent, and shaped by the interaction of visual and verbal elements. The study contributes to the development of modern linguistic theory by proposing an integrated perspective on emoji interpretation.